Metode prepoznave poplavnega stanja pri aeraciji v posodi s turbinskim mešalom - Bombač, Andrej (Strojniški vestnik, 2002)
This article paper presents some appropriate methods for flooding detection by the dispersion of gases into liquids in a stirred vessel equipped with a single Rushton turbine. These methods are based on measurements of global properties, such as mixing-power minimum and gas-holdup maximum, and a method based on the local interfacial characteristics of two-phase systems. The experiments were performed by dispersing air into water and air partly into water-carboxy-methyl cellulose (CMC) solutions of different concentrations. A comparison of the results of the different methods is shown, as well as a comparison with the results from criteria found in the literature.
Keywords: mešala turbinska; stanja poplavna; metode prepoznavanja; dispergiranje zraka; turbinska mešala; dispergiranje; karakteristike; poplavna stanja